ABD’de Yükselen Popülist Dalga ve Trumpizm: Neoliberal Küreselleşme, Ekonomik Kriz, Siyasetin İşlevsizleşmesi ve Elitizme Karşı Bir Geri Tepki mi? - Ömer KURTBAĞ (Gazi Akademik Bakış)
This study attempts to analyse the rise of the neo-populist wave in the US, which is most evident in Donald Trump’s 2016 presidential election victory. Its main argument is that contemporary American populism shares the main traits of populism, such as anti-elitism, the rule of popular will, ideological confusion, and anti-pluralism. Secondly, it contends that the current political landscape of neo-populism has manifested through the decay of a globalised American economy and its fundamental democracy and politics, which demonstrates the need for a major overhaul of the establishment. Thirdly, the study concludes with the observation that populism may play a corrective role in the recovery of the US economy and its politics, and it suggests that if this opportunity cannot be seized then this form of populism could evolve into an illiberal democracy or even authoritarianism